Pemanfaatan Teknologi Untuk Peningkatan Layanan BPJS Pada Perbankan Syariah - Ilmiah, Dunyati; Sani, Ageng Asmara; Wonoseto, Muhammad Galih (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2021)
This research measures and analyzes the use of technology to improve BPJS services in Islamic banking using the Survey on Financial Inclusion and Access SOFIA data. Data was collected in 2017 in four provinces, namely East Java, West Nusa Tenggara, East Nusa Tenggara, and South Sulawesi with a total number of respondents 19,634. The findings in this study reveal that 98.36% of people pay BPJS using the cash method and 1.64% of people use technology. From the data above, it can be concluded that the people in the four provinces are very minimal related to financial inclusion, people prefer to make cash payments rather than using payment service facilities in Islamic banking. The results of this study attracted the attention of policymakers to improve information and education related to financial inclusion.